2001
DOI: 10.1053/jhep.2001.27544
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin gene usage and immunohistochemical characteristics of human monoclonal antibodies to the mitochondrial autoantigens of primary biliary cirrhosis induced in the XenoMouse

Abstract: Antimitochondrial antibodies (AMA) are detected in Ͼ95% of sera from patients with primary biliary cirrhosis (PBC) and recognize the highly conserved mitochondrial 2-oxo-acid dehydrogenase complex (OADC enzyme complex), including the E2 subunit of the pyruvate dehydrogenase complex (PDC-E2), the E2 subunit of the branched-chain 2-oxo-acid dehydrogenase complex (BCOADC-E2), the E2 subunit of the 2-oxoglutarate dehydrogenase complex (OGDC-E2), and E3BP (E3-binding protein or protein X). [1][2][3][4] We hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…21 After transfer, the membranes were processed for immunoblotting as described previously. 21 The primary antibodies for Bmi1 and EZH2 are described above.…”
Section: Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…21 After transfer, the membranes were processed for immunoblotting as described previously. 21 The primary antibodies for Bmi1 and EZH2 are described above.…”
Section: Immunoblottingmentioning
confidence: 99%
“…21 After transfer, the membranes were processed for immunoblotting as described previously. 21 The primary antibodies for Bmi1 and EZH2 are described above. a-Tubulin as an internal control was detected using mouse monoclonal anti-a-tubulin (clone TU-01, Zymed, South San Francisco, CA, USA).…”
Section: Immunoblottingmentioning
confidence: 99%
“…26 After transfer, the membranes were processed for immunoblotting as described previously. 26 The primary antibodies for bmi1 and p21 WAF1/Cip1 are described above.…”
Section: Immunoblottingmentioning
confidence: 99%
“…26 After transfer, the membranes were processed for immunoblotting as described previously. 26 The primary antibodies for bmi1 and p21 WAF1/Cip1 are described above. P16 INK4a and ␣-tubulin were detected by using rabbit polyclonal antibody for p16 INK4a (Santa Cruz Biotechnology, Santa Cruz, CA) and mouse monoclonal anti-␣-tubulin (clone TU-01; Zymed, South San Francisco, CA).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Considering the importance of the CDRs in the antigen binding site and in particular the CDR3, our results of restricted CDR3 features and predominant V 2-14 rearrangements indicated that the V H 3-21 + cases showed signs of a common antigen recognition site. The V H 3-21 gene has been shown to be utilized in certain autoantibodies produced in rheumatoid arthritis, Sjögren's syndrome and primary biliary cirrhosis and, similarly to the V H 1-69 gene, an association with autoreactivity specificities has been shown for this VH gene (60,74,75). However, the V H 3-21/ 2-14 antibody specificity and its role in the development of CLL have yet to be defined.…”
Section: Cll Utilizing the Ig Gene V H 3-21mentioning
confidence: 99%